Assessment of the Quality of Hand-dug Well Water in Lubumbashi, DR Congo: Bacteriological, pH and Temperature Characteristics - Manya, Tsheko; Manun’Ebo, Manu F.; Khang, Esther Imvar; Nkulu-wa-Ngoie, Choudelle (British Journal of Healthcare and Medical Research, 2026)
Background: Access to safe drinking water remains a critical challenge in Lubumbashi, Democratic Republic of the Congo (DR Congo), where a significant proportion of the population relies on hand-dug wells for domestic water supply. This study assessed the bacteriological quality, pH, and temperature characteristics of hand-dug well water in Lubumbashi to determine its suitability for human consumption. Methods: A cross-sectional study was conducted across two neighbourhoods in Lubumbashi from April to June 2024. Eighty-nine water samples were collected from hand-dug wells. Physical parameters (pH, and temperature) were measured in situ using portable instruments. Bacteriological analysis was performed using selective culture media to detect total coliforms, faecal coliforms, Escherichia coli, Salmonella typhi, and Clostridium perfringens. Results were compared with World Health Organization (WHO) and DR Congo national drinking water standards. Results: The median water temperature was 23°C (range: 18-28°C). Waters were predominantly acidic with pH values below 6.5. Overall bacteriological contamination was detected in 38% of samples. Faecal indicators organisms were not identified among the bacterial contaminants of which: Enterobacter agglomerans, Klebsiella ozanae, Klebsiella pneumoniae, and Proteus mirabilis. These signify a potential risk for opportunistic infections and may lead to gastrointestinal disturbances. Conclusion: Hand-dug well water in Lubumbashi exhibits substantial bacteriological contamination, rendering just under two fifths of the samples unsuitable for direct human consumption according to WHO standards. Although the identified pathogens present health risks, their presence may suggest an alternate pathways of contamination—potentially environmental or opportunistic in nature—rather than direct faecal contamination.